Synergies and trade-offs between ecosystem services in Costa Rica - Locatelli, Bruno; Imbach, P. A; Wunder, Sven (Cambridge University Press, 2014)
Ecosystems services have become a key concept in understanding the way humans benefit from ecosystems. In Costa Rica, a pioneer national scheme of payment provides compensation for forest conservation that is assumed to jointly produce services related to biodiversity conservation, carbon storage, water and scenic beauty, but little is known about the spatial correlations among these services. A spatial assessment, at national scale and with fine resolution, identified the spatial congruence between these services, by considering the biophysical potential of service provision and socioeconomic demand. Services have different spatial distributions but are positively correlated. Spatial synergies exist between current policies (national parks and the payment scheme) and the conservation of ecosystem services: national parks and areas receiving payments provide more services than other areas. Biodiversity hotspots have the highest co-benefits for other services, while carbon hotspots have the lowest. This finding calls for cautiousness in relation to expectations that forest-based mitigation initiatives such as REDD (reducing emissions from deforestation and forest degradation) can automatically maximize bundled co-benefits for biodiversity and local ecosystem services.